Effects of processing on the structure of zein/oleic acid films investigated by X-ray diffraction - Wang, Y.; Lopes, F.; Geil, P.; Padua, G. W. (Wiley-Blackwell, 2005)
Zein films plasticized with oleic acid were formed by solution casting, by the stretching of moldable resins, and by blown film extrusion. The effects of the forming process on film structure were investigated by X-ray diffraction. Wide-angle X-ray scattering (WAXS) patterns showed d-spacings at 4.5 and 10 angstrom, which were attributed to the zein alpha-helix backbone and inter-helix packing, respectively. The 4.5.angstrom d-spacing remained stable under processing while the 10 angstrom d-spacing varied with processing treatment. Small-angle X-ray scattering (SAXS) detected a long-range periodicity for the formed films but not for unprocessed zein, which suggests that the forming process-promoted film structure development is possibly aided by oleic acid. The SAXS d-spacing varied among the samples (130-238 angstrom) according to zein origin and film-forming method. X-ray scattering data suggest that the zein molecular structure resists processing but the zein supramolecular arrangements in the formed films are dependent on processing methods.
Keywords: biobased; films; SAXS; structure characterization; WAXS; zein